Does minimally invasive external fixation of proximal humerus fractures provide adequate stability? A biomechanical in vitro study - Markus Greinwald; Franz Matschl; Stephan Regenbogen; Robert Pätzold; Davide Blonna; Peter Augat (BMC Musculoskeletal Disorders)
Abstract Introduction Proximal humerus fractures are usually treated with rigid angle-stable plates or nails. As an alternative, semi-rigid, minimally invasive systems have been developed for supportive fixation. A new system uses this principle with 2.5 mm partially threaded pins and external fixation. Aim This study aimed to compare the fracture stability of the fixator with an angular stable plate about whether the mechanical stability is sufficient for early postoperative mobilisation. Materials and methods Human proximal humeri (paired, female, age ≥ 60, n = 8) were cut to a 3-part fracture and treated with an external fixator (Galaxy Shoulder, Orthofix) or an angular stable plate (Philos, DePuy Synthes). A physiological load was simulated in vitro based on a 45° abduction motion. The load level was continuously increased from 10 to 320 N within 10,000 cycles simulating the loads during rehabilitation. This was followed by another 10,000 cycles at 320 N for fatigue testing. Fracture motion was recorded with a 3D camera. Fracture stability was evaluated at a partial load of 160 N and 240 N (simulating loads during early mobilisation). Results The fracture motion at the lateral aspect was significantly (p < 0.034) larger for the fixator compared to the plate both for axial and for shear movements, while at the medial aspects fracture motions were similar. Both fixation systems adequately stabilized the lateral tubercle fragment with no significant differences between fixation techniques. The migration of the fixator pins (1.1 ± 1.0 mm) and valgus rotation of the head fragment were minimal (3.1 ± 2.0°). The maximum load level of 320 N was reached by all plate constructs and 3 fixator constructs. Conclusion Our results suggest that the external fixator system allows early but gentle postoperative mobilisation. More aggressive rehabilitation measures should be postponed after the healing of the fracture.